(untitled) (Research, Society and Development, 2024)
The exclusion criteria for completing this filtering were: duplicate studies, editorials, articles, case studies, letters to the editor, pilot projects, articles not fully available online and that did not provide sufficient information on the topic. Articles and articles that did not remain external. Examine researchers’ descriptors and identify incomplete texts. Research suggests that there is wide variation in pregnant women’s knowledge about inducing labor and that there are often gaps in their understanding of the procedure and the associated risks. Antenatal education plays an important role in promoting pregnant women’s knowledge about inducing labor. A systematic and individualized educational program is associated with deepening knowledge of this topic in pregnant women. Prenatal education plays a fundamental role in promoting pregnant women’s knowledge about inducing labor. A structured and individualized educational program has been shown to be effective in improving pregnant women’s understanding of this topic. In this sense, it is important that healthcare professionals, especially obstetricians, play a role in educating and guiding pregnant women and providing clear, accurate and evidence-based information.